Peripheral intravenous cannulation: analysis of undergraduate nursing student reports - Samylle Pelaes da Mota; Joice Silva do Nascimento; Shirlane Priscilla Barbosa de Melo Azedo; Camylla Cavalcante Soares de Freitas; Alexsandra Rodrigues Feijão; Gabriela de Sousa Martins Melo (Universidade Federal de Santa Maria, 2019)
Aim:To analyze undergraduate nursing students written report on peripheral intravenous cannulation procedure with catheter. Method: Quantitative, descriptive study, developed with 76 undergraduate nursing students at a public university, from February through March 2014. Data collection took place at simulated scenario and procedure reports were evaluated with a structured instrument. Descriptive analysis was performed. Results: About fragilities, 100% of the students did not wrote about catheter fixation in the report; The variables complications (87,3%), used device (85%) and reason for procedure (84,1%) were predominantly absent. Adequate date, time and identification were positive highlights. Conclusion: Technique registration discrepancies were identified, with essential information being absent or incomplete. This particular subject should be improved with an association between theory and practice, focusing on competence development at teaching environments.